Socio‐demographic and geographical patterns in forest and park use: Insights from 33 European countries - Živojinović, Ivana; Ivanović, Stojan; Tošković, Oliver; Pülzl, Helga; De Vreese, Rik; Davies, Clive; Roitsch, Dennis; Winkel, Georg; Tyrväinen, Liisa; Kronenberg, Jakub; Basnou, Corina; Lovrić, Marko; et al. (John Wiley & Sons, 2026)
Access to (urban) nature is vital for people's wellbeing, but this accessibility is not evenly spread across socio-demographic groups, nor across the European continent. This paper fills a research gap by exploring the use patterns and accessibility of forests and parks across European cities, based on a standardised online survey of 10,462 people from 33 European countries. The results highlight a complex relationship between accessibility, socio-demographic factors and personal motivations in shaping the use of forests and parks. Key findings include variations in visiting patterns by age and gender, with younger individuals and women showing a higher propensity for frequent visits. Motivations for forest and park use varied widely, ranging from physical health and recreation to social interaction and mental well-being. Importantly, the study identified accessibility challenges, particularly travel time, connectivity and limited amenities (e.g. safe walking/cycling routes, lighting, toilets), which limit park and forest use. The results also highlight the diversity in use patterns across different European regions and based on gender, revealing significant variations in how people value and use forests and parks. The study suggests that socio-demographic factors, accessibility and personal motivations play crucial roles in determining forest and park use, underscoring the importance of inclusive urban planning to accommodate diverse needs and preferences.
Keywords: accessibility; Europe; gender; green areas; green infrastructure; motivations; perceptions; survey; forests; parks